Empathy bodyssence: temporal dynamics of sensorimotor and physiological responses and the subjective experience in synchrony with the other’s suffering - Troncoso, Alejandro; Blanco, Kevin; Rivera-Rei, Álvaro; Martínez-Pernía, David (Frontiers in Psychology, 2024)
Background: Empathy is foundational in our intersubjective interactions, connecting with others across bodily, emotional, and cognitive dimensions. Previous evidence suggests that observing individuals in painful situations elicits whole bodily responses, unveiling the interdependence of the body and empathy. Although the role of the body has been extensively described, the temporal structure of bodily responses and its association with the comprehension of subjective experiences remain unclear. Objective: Building upon the enactive approach, our study introduces and examines "bodyssence," a neologism formed from "body" and "essence". Our primary goal is to analyze the temporal dynamics, physiological, and phenomenological elements in synchrony with the experiences of sportspersons suffering physical accidents. Methods: Using the empirical 5E approach, a refinement of Varela's neurophenomenological program, we integrated both objective third-person measurements (postural sway, electrodermal response, and heart rate) and first-person descriptions (phenomenological data). Thirty-five participants watched videos of sportspersons experiencing physical accidents during extreme sports practice, as well as neutral videos, while standing on a force platform and wearing electrodermal and heart electrodes. Subsequently, micro-phenomenological interviews were conducted. Results: Bodyssence is composed of three distinct temporal dynamics.Forefeel marks the commencement phase, encapsulating the body's pre-reflective consciousness as participants anticipate impending physical accidents involving extreme sportspersons, manifested through minimal postural movement and high heart rate. Fullfeel, capturing the zenith of empathetic engagement, is defined by profound negative emotions, and significant bodily and kinesthetic sensations, with this stage notably featuring an increase in postural movement alongside a reduction in heart rate. In the Reliefeel phase, participants report a decrease in emotional intensity, feeling a sense of relief, as their postural control starts to reach a state of equilibrium, and heart rate remaining low. Throughout these phases, the level of electrodermal activity consistently remains high.This study through an enactive approach elucidates the temporal attunement of bodily experience to the pain experienced by others. The integration of both first and third-person perspectives through an empirical 5E approach reveals the intricate nature of bodyssence, offering an innovative approach to understanding the dynamic nature of empathy